r-65/3=6

Simple and best practice solution for r-65/3=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for r-65/3=6 equation:


r in (-oo:+oo)

r-(65/3) = 6 // - 6

r-(65/3)-6 = 0

r-65/3-6 = 0

r-83/3 = 0 // + 83/3

r = 83/3

r = 83/3

See similar equations:

| 6w+w=56 | | 1/8(8x-6)=-1/4-9/4 | | 28+3p=56 | | 4x+6+2x=25+5x-7 | | 40=15u-7u | | 1900=10x+10y | | xyz=140 | | 5x+10=7-2 | | 3e^2x+5=1100 | | 10+3x=4x-11 | | 3x-2x=-12-4 | | 27-x=167 | | 9m-16=15 | | Y^2=4.8(x-1) | | 25-5x=x-5 | | x+15*x=100 | | 18n=64 | | -4k=-9+5k | | x=1/2(8x-24) | | 8x-3(2x-1)=2x+4 | | 8a^2+19a+6= | | 8q+9=5q | | 3n^2-25=0 | | 8x+3(2x-1)=2x+4 | | 2(13-x)=4(8-x) | | 7x-28/8x-48 | | 9-2k-3k=-1 | | x^2-8x+y^2-10y=-25 | | 5z-3/z-1 | | 5x-5-2x=9x+3-7x | | x=4(-2)+14 | | log8x=-1/3 |

Equations solver categories